Attention and achievements in the IT industry today - Kuvandikova Damegul Kazakbaevna; Azbergenova Ayzada Kabilbay qizi; Avezbayeva Ozoda Po'lat qizi (Zien Journals, 2023)
Today, the development of the entire state is directly related to the development of the IT sector, so many countries around the world focus primarily on creating favorable conditions for improving the entire IT ecosystem
Keywords: development; opportunity; attention; conditions